2021
DOI: 10.15252/msb.202010064
|View full text |Cite
|
Sign up to set email alerts
|

Global coordination of metabolic pathways in Escherichia coli by active and passive regulation

Abstract: Microorganisms adjust metabolic activity to cope with diverse environments. While many studies have provided insights into how individual pathways are regulated, the mechanisms that give rise to coordinated metabolic responses are poorly understood. Here, we identify the regulatory mechanisms that coordinate catabolism and anabolism in Escherichia coli . Integrating protein, metabolite, and flux changes in genetically implemented catabolic or anabolic limitations, we show that combined g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 96 publications
(150 reference statements)
3
28
0
Order By: Relevance
“…Due to this trade-off, natural selection may have favored the evolution of an approximate, robust implementation of the optimal enzyme–metabolite balance, potentially explaining why enzyme concentrations are roughly constant across conditions ( Fig 3A ). Moreover, a trade-off between enzyme–metabolite optimality and regulatory costs may also be consistent with the observation that protein concentration changes across growth conditions are often regulated not at the level of each individual protein, but at the level of complete pathways or protein sectors [ 2 , 21 , 34 , 35 ], controlled by global factors such as Crp [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
“…Due to this trade-off, natural selection may have favored the evolution of an approximate, robust implementation of the optimal enzyme–metabolite balance, potentially explaining why enzyme concentrations are roughly constant across conditions ( Fig 3A ). Moreover, a trade-off between enzyme–metabolite optimality and regulatory costs may also be consistent with the observation that protein concentration changes across growth conditions are often regulated not at the level of each individual protein, but at the level of complete pathways or protein sectors [ 2 , 21 , 34 , 35 ], controlled by global factors such as Crp [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
“…Control systems acting on the transcriptome, proteome, and metabolome or on the “interactome” that spans all three are typically thought of as mechanisms and not as information-processing systems that display active intelligence. (However, see [ 68 ], in which metabolite regulation of metabolic pathways is characterized as “heuristic”, and [ 69 ], in which the consequences of metabolic decisions are considered in development and disease.) These and other biological phenomena can, however, be cast as behavior and problem solving in appropriate spaces, such as the transcriptional and physiological spaces depicted in Figure 2 A,B, respectively.…”
Section: Transcriptional Metabolic and Physiological Spacesmentioning
confidence: 99%
“…It is not known yet how the planaria do this, but one possibility involves generalization (one dimension of intelligence) to recognize barium-induced physiological states as belonging to a class of other problems (like excitotoxicity) for which planarian cells may have evolved solutions. Perhaps, like bacterial metabolism sensing systems [ 68 , 76 , 77 ], the cells detect (and act on) highly processed state information several steps removed from the proximal events at the membrane. In this case, the many ways to depolarize tissue could be naturally coarse-grained to represent a single problem: a change in membrane voltage addressable by a single set of transcriptional actions.…”
Section: Transcriptional Metabolic and Physiological Spacesmentioning
confidence: 99%
“…Despite close coordination of metabolic flux at different interfaces between CcpA and CodY reactions, it is still not clear how CcpA and CodY activities are coordinated. In E. coli , Kochanowski et al have observed similar coordination between anabolic and catabolic fractions of metabolism 46 . The authors attributed active regulation by Crp and passive changes in metabolic fluxes in response to change in metabolite concentrations as the source of the coordination.…”
Section: Discussionmentioning
confidence: 94%